Upcycle Jaket Denim Sebagai Media Eksplorasi Teknik Slashing Kombinasi Limbah Perca Sumber Ide Fireworks - Ayu Artamevia Katerina Putri; Yuhri Inang Prihatina (Universitas Negeri Surabaya, 2025)
The slashing technique is a technique of manipulating the fabric by sewing several piles of fabric and then cutting according to the bias while still showing the bottom layer. This study aims to find out the process of exploring the design and finished results of the denim jacket upcycle as a medium for exploring slashing techniques in combination with patchwork waste and fireworks ideas. The research method using the double diamond method includes 4 stages: Discover collects information about the final effect of fireworks and designs slashing motif exploration, Define creates a moodboard